Diseño de la ingeniería inmótica de laboratorios del bloque 3 - Sede Queri de la Universidad de las Américas - Alabuela Escobar, Mauricio Francisco (2018)
The aim of this thesis is to present the Design of Inmotic Engineering for the laboratories of Block 3 of the Queri Headquarters at the University of the Americas, integrating inmotic technologies capable of automating different areas. For the development of the present project, the requirements and needs of the University are analyzed through visits to the laboratories and interviews with the coordinator of the faculty and the energy efficiency group of the FICA (Faculty of Engineering and Agricultural Sciences), where define the areas of lighting, comfort, safety, and energy consumption that the University requires. The existing inmotic technologies such as BACNET, KNX / EIB, LONWORKS, BUSING are analyzed and according to the characteristics and requirements, the most suitable technology will be selected through a comparative analysis. Architectural plans represent the inmotic devices with their respective connections and location. For the electrical supply of each device it is necessary to reengineer electrical connections for each area. In the cost and benefit analysis, the value is detailed for each area of the project, in such a way that it allows to have a budget, through mathematical calculations, percentages and evaluations the profitability is determined against the total investment of the project. For the analysis of the cost of lighting, the total calculation of the energy consumption of luminaires in a laboratory is made, with the inmotic system a saving of 34 por ciento in the total monthly energy consumption in lighting in each laboratory is estimated. With an investment of 2024.09 dollars in the control system and inmotic security, the value of 21,700 dollars is guaranteed in the valuation of computer equipment in a laboratory. obtaining a return of 81 percent. The cost of the sound and multimedia inmotic system is 20148.14 dollars in the whole Block 3 of the Queri Campus, this will reduce up to 25 percent the academic stress of students and allows an increase in academic and work performance by 20 percent. The total investment of the inmotic energy consumption system is 3790.61 dollars in the whole Block 3 of Queri Headquarters, this allows to monitor the electrical consumption of each area, obtaining an economic saving of up to 10 percent in repairs and maintenance in an approximate time of up to 10 years.